2020
DOI: 10.1142/s179360472040007x
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanoparticles with iron impurities for multifunctional applications

Abstract: Crystalline silicon (Si) nanoparticles (NPs) doped with iron (Fe) in the range from 0.02 to 2.5 at.% were prepared by plasma-ablative synthesis and were investigated by means of the transmission electron microscopy, X-ray diffraction (XRD), dynamic light scattering (DLS), infrared spectroscopy and nuclear magnetic resonance relaxometry. While the nanocrystal size in Si:Fe NPs did not depend significantly on Fe content, the hydrodynamic diameter of NPs in aqueous suspensions increases from 50 to 180[Formula: se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
6
0
4
Order By: Relevance
“…While the intratumoral injection induces the stronger antitumor effect, the observed decrease in tumor volume after intravenous administration confirms accumulation of Si NPs in the tumor due to as-called enhanced permeability and retention effect, which is well known for various NPs [105]. It was found that the antitumor effect of iron-doped Si NPs correlate with lifetime of laboratory animals [103]. Figure 42 shows temporal dependences of the number of mice with cancer tumor after intravenous and intratumoral administration of NPs.…”
Section: Si Nps With Electron Spin Centers As Potential Contrast Agenmentioning
confidence: 63%
See 4 more Smart Citations
“…While the intratumoral injection induces the stronger antitumor effect, the observed decrease in tumor volume after intravenous administration confirms accumulation of Si NPs in the tumor due to as-called enhanced permeability and retention effect, which is well known for various NPs [105]. It was found that the antitumor effect of iron-doped Si NPs correlate with lifetime of laboratory animals [103]. Figure 42 shows temporal dependences of the number of mice with cancer tumor after intravenous and intratumoral administration of NPs.…”
Section: Si Nps With Electron Spin Centers As Potential Contrast Agenmentioning
confidence: 63%
“…As for the second line of intrinsic Si DBs they are supposed to be localized in SiO 2 surface coating of the NP surfaces, which was confirmed by X-ray photoelectron spectroscopy and FTIR measurements [101]. Furthermore, HR-TEM images of iron doped Si NPs reveal numerous defects of the crystalline structure as twins and grain boundaries related to the fast cooling rate during their formation in argon flow [103]. Both the iron impurities and intrinsic defects as Si DBs are responsible for the large number of electron spin centers in such NPs [101,103].…”
Section: Si Nps With Electron Spin Centers As Potential Contrast Agenmentioning
confidence: 67%
See 3 more Smart Citations